Evaluation vs landscape planning in the Italian framework: Is the risk prevention a utopia? - Cialdea, Donatella (TeMA - Journal of Land Use, Mobility and Environment, 2021)
Territorial management can be implemented through an intervention perspective concerning a plurality of characteristics inherent to natural and artificial resources, in order to guarantee protection of environmental and territorial identity. The thesis, to be addressed in this paper, concerns the question of whether landscape planning is able to prevent and protect against the risks deriving from poor management of the territory. In particular, in Italy the Landscape Plan, in the role it assumes under the so called Urbani Code, recognizes the value of the territories in an attempt to direct the safeguarding and restoration of landscape values. In this paper the role of Strategic Environmental Assessments in the prevention of risks in the hypothesis of reasonable alternatives has been analysed.